Fatigue damage assessment of offshore riser subjected to vortex-induced vibrations by SHEAR7 - Lekkala, M.R. (Society of Naval Architects of Korea, 2022)
Marine risers are a critical component in transporting the produced hydrocarbons from the seabed to the topside facility and vice versa. These risers are subjected to VIV when encountered with ocean currents, leading to the accumulation of fatigue damage, which reduces the risers' service life. Estimation of fatigue damage is an important aspect to assure reliable and operable conditions. SHEAR7 is used in this analysis to estimate the fatigue damage of the Top Tensioned Riser (TTR). SHEAR7 is widely used semi-empirical software in the offshore industry to estimate the fatigue damage induced by VIV. Recently, SHEAR7 has been revised to account for the higher harmonic corrections based on experimental and field data. The key pertaining to the revision of adding higher harmonics can contribute 50 higher strain along the length of the riser at some locations (Jhingran and Vandiver, 2007). VIV fatigue damage analysis was conducted using SHEAR7 v4.7b and v4.9b to investigate the effect of the higher harmonics considered in the later version. The TTR model used in this analysis was modelled in OrcaFlex and validated with available references in the literature. TTR with different model scenarios was developed, and comparisons were made between the predicated responses from SHEAR7 v4.b and v4.9b for the riser. It was observed that higher harmonic correction factors have a great impact on the performance of the riser. Finally, sensitivity analyses were carried out to check the effect of individual parameters and higher harmonic correction factors on predicted responses between the two versions of SHEAR7. Â© 2022